Impacts of Social Media on Public Policy Development in pre-Taliban Afghanistan (Global Media Journal - German Edition, 2024)
The impacts of media, mainly social media, have attracted greater scholarly attention. However, their effects on public policy development and the decision-making procedure of a government have not been examined so far. Thus, this study examines such effects in pre-Taliban Afghanistan before August 2021. Theories of signal detection and agenda-setting are adopted. Five variables (problem identification, media attention, perceived change, social media intensity, and relevance of social media) were conceptualized and operationalized to understand and measure the impact. Two data sets, qualitative and quantitative, were chosen on the eve of a presidential election (September 2019). For the first data set, a 63-question questionnaire was developed and piloted, and a purposive sample was chosen (N = 385). The second set contains in-depth interviews with government employees and bloggers. Findings show that social media influences public policy formulation and decision-making procedures. The results further reveal that social media are an essential vehicle for governance, have the potential to provide a networked public sphere, and bridge the communication gap between government and the public in a fragile state like Afghanistan.
Keywords: social media; effect of social media; public policy; agenda-setting; Facebook; Twitter